Intellectual Hegemony, Conversion Discourse and Early Christian Apologetic Literature - Adrahtas, Vassilios (Religions, 2021)
The present study aspires to catch a glimpse of a peculiar phenomenon in the history of religions, namely, the competitive character of early Christian apologetic literature in its attempt to confront head-on the non-Christian ideological life-world and, for that matter, to persuade the latter’s adherents to convert to the new hierophanic message. More specifically, in this study I look into the hierophanic/religious/spiritual market of the first three centuries CE, focusing on its creating, perpetuating and promoting of intellectual hegemony interactions, while at the same time I explore the conversion discourse used by all parties concerned in order to win over the Other. Apart from other religions, early Christian ‘Apologists’ faced predominantly Middle Platonism, Stoicism, Neopythagoreanism and, last but not least, Neoplatonism. In doing so they adopted a number of rhetoric and social strategies at hand; strategies that, although intended to turn the Other into the Same—which they did achieve, albeit gradually—ended up turning the Same into the Other as well.